2005
DOI: 10.1002/art.20947
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging evidence of tendinopathy in early rheumatoid arthritis predicts tendon rupture at six years

Abstract: Objective. To determine whether magnetic resonance imaging (MRI) evidence of tendinopathy in early rheumatoid arthritis (RA) could be used to predict the course of tendon involvement in later disease and specifically the risk of tendon rupture.Methods. The occurrence, pattern, and progression of tendinopathy were studied prospectively over 6 years in a cohort of patients who had presented with RA. Of 42 patients enrolled, full MRI and clinical data were available for 31 at 6 years. MRI scans of the dominant wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 19 publications
(26 reference statements)
1
44
1
1
Order By: Relevance
“…Mc Queen et al report tenosynovitis in the dominant wrist, especially in the first year of disease, to be a frequent finding found at MRI examinations [37]. Indeed, another MRI based longitudinal study conducted by Lindegaard et al concluded that tenosynovitis in the dominant wrist and at MCF level was present in about 60 % of the ERA patients at baseline with reduction to 28% after 6 months and a yearfollow-up, showing a good response to therapy superior to the synovitis response [38].…”
Section: Clinical and Imaging Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…Mc Queen et al report tenosynovitis in the dominant wrist, especially in the first year of disease, to be a frequent finding found at MRI examinations [37]. Indeed, another MRI based longitudinal study conducted by Lindegaard et al concluded that tenosynovitis in the dominant wrist and at MCF level was present in about 60 % of the ERA patients at baseline with reduction to 28% after 6 months and a yearfollow-up, showing a good response to therapy superior to the synovitis response [38].…”
Section: Clinical and Imaging Evaluationmentioning
confidence: 98%
“…Moreover, MSUS has been considered by some authors as the "goldstandard" method for the evaluation of superficial tendons [45]. In comparison to MRI it permits not only multi-planar evaluation but also real time dynamic assessment and vasculariza-Overall, MSUS showed a fair to moderate sensitivity but a high specificity [28,29,31,33,37,46,[60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Clinical and Imaging Evaluationmentioning
confidence: 99%
“…Tenosynovitis is common in RA [Hmamouchi et al 2011] but its true prevalence in early disease has not been firmly established. A complication of persistent tenosynovitis is complete rupture of the tendon with loss of function [Mcqueen et al 2005]. Tenosynovitis can be difficult to diagnose clinically in patients with arthritis as pain could easily be attributed to underlying joint involvement.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…MRI of a single wrist in patients with early rheumatoid arthritis (evaluated for bone edema and total rheumatoid arthritis abnormalities), however, has been demonstrated to predict the physical function subscale of the Short Form-36 at 6 years of follow-up [49]. In the same cohort, MRI tendinopathy at baseline also predicted tendon rupture at 6 years, although the cohort was small [50].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 96%